Contemporary Muslim-Christian encounters: developments, diversity, and dialogues - Hedges, Paul (Bloomsbury Academic, 2015)
Preface, Leonard Swidler (Temple University, USA) -- Forward, Alan Race (University of Winchester, UK) -- 1. Dialogue before Dialogue, David Thomas (University of Birmingham, UK) -- 2. The Contemporary Context of Muslim-Christian Dialogue, Paul Hedges (University of Winchester, UK) -- 3. Can those Chosen by God Dialogue with Others?, Reuven Firestone (University of Southern California and Hebrew Union College, USA) -- 4. Interreligious Dialogue as Lay, Institutional, and Academic: Muslim Perspectives, Khaleel Mohammed (San Diego State University, USA) -- 5. Gender and Muslim-Christian Dialogue, Anne Hege Grung (University of Oslo, Norway) -- 6. Applying Sharia Principles of Religious Tolerance to the Protection of Children: Nigerian Religious Conflict and Reconciliation amongst Muslims and Christians, Yusuff J. Amuda (International Islamic University, Malaysia) -- 7. Peace-building Through Interfaith Dialogues: The DRC Model, Jean-Daniel Kabati (University of Kwazalu Natal, South Africa) -- 8. Initiative and Response: The Future of Muslim-Christian Dialogue, Douglas Pratt (University of Waikato, New Zealand, and University of Bern, Switzerland) -- 9. Christian Responses to Islamophobia, Ray Gaston (Queen's Foundation for Ecumenical Theological Education, UK) -- 10. Christian Muslim Relations in the USA: A Postmodern Analysis after 9/11, Clinton Bennett (State University of New York, USA) -- 11. 'Bringing Faith Back In': Muslim and Christian Approaches to Nuclear (Non-)Proliferation and Disarmament, Shirin Shafaie (School of Oriental and African Studies (SOAS), University of London, UK) -- 12. Vatican and World Council of Church Initiatives: Weaving Interreligious Threads on Ecumenical Looms, Clare Amos (World Council of Churches) -- Bibliography -- Index.